Sexual and reproductive health service utilization among patients with podoconiosis in Wolaita Zone, South Ethiopia: a multilevel mixed-effect analysis - Temesgen Lera Abiso; Amene Abebe Kerbo; Eskinder Wolka Woticha (Frontiers in Reproductive Health)
BackgroundSexual and reproductive health (SRH) services are essential for promoting the wellbeing of individuals and communities. Achieving universal health coverage is unattainable without ensuring equitable access to SRH services and upholding sexual and reproductive rights. Podoconiosis, a neglected tropical disease and non-filarial form of elephantiasis, is caused by prolonged barefoot exposure to irritant volcanic soils. Although SRH services have been increasingly integrated into primary healthcare systems in Ethiopia, people affected by podoconiosis continue to face substantial barriers in accessing these services due to stigma, mobility limitations, and socioeconomic constraints. In this context, the present study aims to assess the utilization of SRH services and the factors associated with their utilization among patients with podoconiosis in Wolaita Zone, South Ethiopia.MethodsA community-based cross-sectional study was conducted among 836 patients with podoconiosis in Wolaita Zone from 12 November to 20 December 2024. Multistage sampling was used to select participants, and data were collected through face-to-face interviews. A multilevel logistic regression analysis was performed to identify the factors associated with SRH service utilization. Statistical significance was set at p < 0.05, and adjusted odds ratios (AOR) with 95% confidence intervals (CI) were reported.ResultsThe study found that 154 respondents (18.4%; 95% CI: 16%, 21%) utilized SRH services within the past 12 months. The factors significantly associated with SRH service utilization included the following: age groups 18–29 years (AOR = 3.57; 95% CI: 1.55–8.25), 30–34 years (AOR = 2.89; 95% CI: 1.30–6.40), and 35–39 years (AOR = 5.06; 95% CI: 2.45–10.45); prior experience with health services (AOR = 2.39; 95% CI: 1.56–4.93); family awareness of podoconiosis etiology (AOR = 3.60; 95% CI: 2.13–6.21); positive attitude toward SRH services (AOR = 5.80; 95% CI: 3.16–10.70); family support (AOR = 2.47; 95% CI: 1.47–4.14); and autonomy in using household financial resources for healthcare (AOR = 2.05; 95% CI: 1.18–3.57).ConclusionThe utilization of SRH services among patients with podoconiosis was found to be low. The significant factors associated with SRH service utilization included the age of respondents, prior experience with health services, family awareness of podoconiosis etiology, family support, autonomy in using household financial resources for healthcare, and positive attitudes toward SRH services.